Developing an Emotion Regulation Training Protocol and Examining Its Effectiveness on Internet Addiction among Female Students - Kheiripour , Fataneh; Bahrami Hidaji , Maryam; Mohammadi shirmahaleh, Fatemeh; Rafezi , Zohreh; Asgharpour , Mania (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: The present research aimed to develop an emotion regulation training protocol and to examine its effectiveness on internet addiction among female students.Methods and Materials: The methodology of this study was quasi-experimental, utilizing a pre-test-post-test design with a control group and a follow-up period. The population consisted of all internet-using female high school students in Islamshahr in the year 2021 (ages 15 to 18). The sample size was 100 individuals, randomly assigned to either the experimental or control groups. The General Health Questionnaire (Goldberg, 1972) and the Sensitivity to Reinforcement Questionnaires (Gray, Jackson, 2009) were administered before and after the training sessions to the respective groups. The analysis of findings was conducted using a mixed-methods approach.Findings: The analysis indicated that emotion regulation training led to a reduction in internet addiction (P = 0.001).Conclusion: Consequently, it can be stated that employing an emotion regulation approach can be effective in reducing internet addiction among students.